Investigation on the barriers of green building development in Malaysia / Nur Nadzirah Roslee, Asniza Hamimi Abdul Tharim and Noraidawati Jaffar - Roslee, Nur Nadzirah; Abdul Tharim, Asniza Hamimi; Jaffar, Noraidawati (Universiti Teknologi MARA, Perak, 2022)
Sustainable development provides environmental and human health benefits, but the development faces obstacles to green building implementation in construction projects. Therefore, the objective of this paper is to determine the barriers and strategies in developing green buildings in Malaysia. For this research, the method used was the quantitative method by using a questionnaire survey. The respondents of this research were contractors ranging from G5 to G7 located in Selangor and Kuala Lumpur. The findings showed that the main barriers of green building development could be classified into two main categories, which are internal barriers and external barriers. The result revealed that a lack of public awareness of the benefits of green building, lack of financial help or government incentives for green building projects, and lack of knowledge about green building were crucial factors restricting green building development in Malaysia. Besides, the strategies to improve green development are also being analysed. Further study suggests the study on green building development in more depth, focusing on a specific type of building.